Differences in IV alcohol-induced dopamine release in the ventral striatum of social drinkers and nontreatment-seeking alcoholics - Yoder, Karmen K. (Drug Alcohol Depend, 2016)
BACKGROUND: Striatal dopamine (DA) has been implicated in alcohol use disorders, but it is still unclear whether or not alcohol can induce dopamine release in social drinkers. Furthermore, no data exist on dopamine responses to alcohol in dependent drinkers. We sought to characterize the DA responses to alcohol intoxication in moderately large samples of social drinkers (SD) and nontreatment-seeking alcoholics (NTS). METHODS: Twenty-four SD and twenty-one NTS received two [(11)C]raclopride (RAC) PET scans; one at rest, and one during an intravenous alcohol infusion, with a prescribed ascent to a target breath alcohol concentration (BrAC), at which it was then “clamped.” The alcohol clamp was started 5 min after scan start, with a linear increase in BrAC over 15 min to the target of 80 mg%, the legal threshold for intoxication. Target BrAC was maintained for 30 min. Voxel-wise binding potential (BP(ND)) was estimated with MRTM2. RESULTS: IV EtOH induced significant increases in DA in the right ventral striatum in NTS, but not SD. No decreases in DA were observed in either group. CONCLUSIONS: Alcohol intoxication results in distinct anatomic profiles of DA responses in SD and NTS, suggesting that in NTS, the striatal DA system may process effects of alcohol intoxication differently than in SD.